GAMBARAN STATUS GIZI BALITA DI KABUPATEN KERINCI TAHUN 2025 - Laras Eka Nurhasanah; Afifah Istiqomah; Winda Sauci Br. panjaitan; Hilda Diniyati (Jurnal Penelitian Kesmasy, 2026)
Introduction: The nutritional status of children under five is an important indicator in assessing the level of public health and the success of health development. Nutritional problems in toddlers such as malnutrition, stunting and overnutrition are still a concern because they have an impact on children's growth and development. This research aims to determine the nutritional status of toddlers in Kerinci Regency in 2025. Method: This research is a descriptive study with a cross sectional approach using secondary data from the Integrated SIGIZI application. The number of samples in this study was 14,085 toddlers. Assessment of nutritional status is carried out based on indicators of body weight for age (WW/U), height for age (TB/U), and body weight for height (WW/TB). Data analysis was carried out descriptively by presenting frequency distributions and percentages. Result: The research results showed that the majority of toddlers had normal nutritional status, namely 13,122 toddlers (93.2%). There were 438 underweight toddlers based on the BB/U indicator (3.2%). There are 425 toddlers in the short category based on TB/U (3.0%). There were 94 toddlers with malnutrition status based on BW/TB (0.7%) and 6 toddlers with malnutrition (0.0%). Conclusion: This research shows that the nutritional status of toddlers in Kerinci Regency is generally classified as good because it is dominated by the normal category, however, both chronic and acute nutritional problems are still found so that routine growth monitoring, nutritional education to parents, and sustainable nutritional interventions are still found to improve the nutritional status of toddlers. Key words: nutritional status, toddlers, BB/U, TB/U, BB/TB, Kerinci Regency.